Clinical outcomes following bifurcation double‐stenting with bioresorbable scaffolds. Issue 6 (17th May 2016) - Tanaka, Akihito; Latib, Azeem; Kawamoto, Hiroyoshi; Jabbour, Richard J.; Mangieri, Antonio; Pagnesi, Matteo; Montalto, Claudio; Regazzoli, Damiano; Ancona, Marco; Chieffo, Alaide; Carlino, Mauro; Montorfano, Matteo; et al.
Abstract : Objectives: To investigate outcomes following bifurcation double‐stenting utilizing a bioresorbable scaffold (BRS) in the main branch (MB) and either a BRS or metallic drug‐eluting stent (DES) in the side branch (SB). Backgrounds: Data on outcomes of bifurcation lesions treated with BRSs, especially with double‐stenting, are currently lacking. Methods: Data were examined from 42 de novo bifurcation lesions (41 patients) treated with double‐stenting utilizing Absorb BRS in MB and BRS/DES in SB. Clinical outcomes including cardiac death, follow‐up myocardial infarction, target lesion revascularization (TLR), and definite scaffold/stent thrombosis (ST) were investigated. Results: The majority of target lesions were left anterior descending artery (LAD) bifurcations, and intravascular imaging was used in the majority of cases (92.9%). In SBs, BRSs were utilized in 19 lesions (19 patients) and DESs in 23 lesions (22 patients). Angiographic success was achieved in all lesions. The median follow‐up was 594 days (interquartile range 214 − 838 days). The overall TLR‐rates were 9.7% at 1 year and 14.0% at 2 years (MB‐TLR: 6.9% at 1 year and 11.1% at 2 years; SB TLR: 9.7% at 1 year and 14.0% at 2 years). No definite ST was observed during follow‐up. TLR rates in both the MB and SB tended to be higher in the SB‐BRS group when compared to the SB‐DES group. Conclusion: Mid‐term clinical outcomes following double‐stenting using BRS were acceptable. Bifurcation lesions treated with DES in SB tended to have lower TLR rates in both the MB and SB when compared to implanting BRS in both branches. © 2016 Wiley Periodicals, Inc.